Molecular Signatures of -Mutated Lung Adenocarcinoma: Analysis of Concomitant , , , and PD-L1 Status - Jim Hsu; Joseph F Annunziata; Ethan Burns; Eric H Bernicker; Randall J Olsen; Jessica S Thomas (SAGE Publishing, 2022)
Background: KRAS mutations are the most common oncogenic driver mutations of non-small cell lung cancer (NSCLC) in the Western world. Mutations of the KRAS gene are most prevalent in the patient population of current and former cigarette smokers. With the recent pivotal approval of a targeted inhibitor therapy for patients with KRAS p.G12C mutated and pretreated NSCLC, analysis of the heterogeneity of KRAS mutations and concomitant molecular alterations in patients with these tumors at all clinical stages is indicated. Methods: In this retrospective analysis, patient pathology records were reviewed for all cases receiving a pathologic diagnosis of NSCLC within our hospital system. All data were collected with IRB approval. Cases of indeterminate tumor type favoring a non-lung primary, as well as non-adenocarcinoma NSCLC (eg, squamous) were excluded from the cohort. In this hospital system, molecular testing for KRAS mutations is part of a molecular biomarker panel that is reflex ordered at initial diagnosis by the pathologist and may be performed as a single gene test or as a solid organ cancer hotspot panel by next generation sequencing. For each patient, KRAS mutational status and specific KRAS mutations, if present, were collated. Additional information assessed for this study included patient demographics (age, gender, and smoking history), tumor staging if available, PD-L1 expression levels by immunohistochemistry (IHC), and the presence of other genetic alterations ( EGFR , ALK , and STK11 ). Results: Between January 1, 2017 and January 1, 2019, there were 276 patients diagnosed with NSCLC of all stages who had KRAS mutational analysis performed in our hospital system and who met the criteria for inclusion into the study cohort. A KRAS driver mutation was detected in 29% of these patients. The most frequently identified KRAS mutation was p.G12C (38%), followed by p.G12D (21%) and p.G12V (13%). KRAS- mutated lung adenocarcinoma was significantly associated with current or former patient smoking status in this cohort (29/202 (14%) smokers and 1/74 (1%) non-smokers; P  = .0006). PD-L1 expression of at least 1% by IHC was present in 43% of KRAS -mutated lung adenocarcinomas and 45% of non- KRAS -mutated adenocarcinomas. In this study, KRAS mutations were not found to co-occur with gene alterations in EGFR , ALK , or STK11 . In 48% of cases, at least one genetic alteration ( KRAS , ALK , EGFR , or STK11 ) was identified. Conclusions: In this study cohort, KRAS -mutated lung adenocarcinoma demonstrated significant mutational heterogeneity, which is consistent with previously published studies. KRAS mutational status was also significantly associated with a current or former smoking history. Notably, p.G12C was the most frequently identified KRAS mutation in this cohort, with a frequency of 38%. This finding is particularly relevant given the recent approval of a KRAS p.G12C-specific targeted inhibitor therapy and the continued development of additional KRAS targeted therapies that may prove effective in treating NSCLC. These findings also highlight the necessity of considering molecular testing for KRAS mutations in patients with NSCLC and a smoking history, as this population most frequently harbors KRAS mutations and may benefit from these emerging targeted therapies.